2016
DOI: 10.18632/oncotarget.12522
|View full text |Cite
|
Sign up to set email alerts
|

CCR10/CCL27 crosstalk contributes to failure of proteasome-inhibitors in multiple myeloma

Abstract: The bone marrow microenvironment plays a decisive role in multiple myeloma progression and drug resistance. Chemokines are soluble mediators of cell migration, proliferation and survival and essentially modulate tumor progression and drug resistance. Here we investigated bone marrow-derived chemokines of naive and therapy-refractory myeloma patients and discovered that high levels of the chemokine CCL27, known so far for its role in skin inflammatory processes, correlated with worse overall survival of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our nding is consistent with previous literature indicating that CCR10/CCL27 myeloma-stroma crosstalk contributes to bortezomib resistance in MM cell lines. 27 In fact, blocking CCR10 signi cantly reduced the proliferative effect of TET2 mutated CH on MM cells, suggesting a potential therapeutic target. Recent surface proteomic analysis also suggests CCR10 as an important molecule in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Our nding is consistent with previous literature indicating that CCR10/CCL27 myeloma-stroma crosstalk contributes to bortezomib resistance in MM cell lines. 27 In fact, blocking CCR10 signi cantly reduced the proliferative effect of TET2 mutated CH on MM cells, suggesting a potential therapeutic target. Recent surface proteomic analysis also suggests CCR10 as an important molecule in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, treatments that enhance the production of these two chemokines have been shown to have anti-cancer properties ( Refs 30,31,32). In contrast, numerous studies have shown that expression of CCL27 and CCL28 was increased in lymphomas, bladder cancer, hepatocellular carcinoma (HCC) and multiple myeloma ( Refs 33,34,35,36,37,38,39,40,41,42,43). Although the underlying mechanisms regarding dysregulation of CCL27/ CCL28 have not yet been defined in all experiments, some studies have indicated possible mechanisms which are discussed in the following.…”
Section: Expression Of Ccr10/ccl27-ccl28 In Cancermentioning
confidence: 99%
“…It is concluded that blocking the CCR10/CCL27/IL-10-dependent myeloma crosstalk with stroma by siRNAs or antibodies might be a novel and tailored therapeutic target in early refractory myeloma patients (Ref. 43).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation